Islamic Rural Bank: Main Drivers of Micro, Small and Medium Enterprises Growth - Rakhman, Kausar Icha Aina; Nisa, Siti Karomatun; Haya, Aina Fathia; Asytuti, Rinda (Jurusan Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Siliwangi, 2023)
Limited capital, production techniques, marketing, management, and technology generally trap MSMEs. MSMEs is a business sector that contributes positively to the economy and experiences problems in capital; the Government provides financial institutions that handle the sector, one of which is BPRS. This research covers the role of BPRS in increasing the growth of MSMEs. This research method uses a descriptive qualitative approach with primary data obtained from interviews with BPRS. Islamic rural bank (called as BPRS) is vital in supporting the real sector, especially MSME. Despite focusing on Islamic financing, challenges such as the need for guarantees and strict procedures can be obstacles for MSMEs in obtaining capital. Although BPRS assists such as training and coaching, MSME adoption of these initiatives is often limited. In facing this complexity, strong cooperation between BPRS, the Government, and MSMEs is needed to advance this sector.UMKM pada umumnya terjebak oleh keterbatasan modal, teknik produksi, pemasaran, manajemen, dan teknologi. UMKM sebagai sektor usaha yang berkontribusi positif terhadap perekonomian dan mengalami permasalahan dalam permodalan, pemerintah menyediakan lembaga keuangan yang menangani sektor tersebut, salah satunya BPRS. Penelitian ini membahas tentang peran BPRS dalam meningkatkan pertumbuhan UMKM. Metode penelitian ini menggunakan pendekatan kualitatif deskriptif dengan data primer yang diperoleh dari hasil wawancara dengan pihak BPRS. Bank pembiayaan rakyat syariah (BPRS), memiliki peran vital dalam mendukung sektor riil khususnya UMKM. Meskipun memiliki fokus pada pembiayaan syariah, tantangan seperti perlunya jaminan dan prosedur yang ketat dapat menjadi kendala bagi UMKM dalam memperoleh modal. BPRS memberikan bantuan seperti pelatihan dan pembinaan, namun adopsi UMKM terhadap inisiatif ini seringkali terbatas. Dalam menghadapi masalah ini, kerja sama yang kuat antara BPRS, pemerintah, dan UMKM sangat diperlukan untuk memajukan sektor ini.